2020
DOI: 10.3390/jcm9010202
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Anti-HBc: Significance and Management

Abstract: Hepatitis B virus (HBV) infection is prevalent worldwide and is associated with dramatic levels of morbidity and mortality. Isolated anti-HBc (IAHBc) is a particular serological pattern that is commonly found in immunocompromised patients. There is ongoing debate regarding the management of patients with IAHBc. Herein, we summarize the current guidelines and the newest evidence. The frequency of IAHBc is variable, with a higher prevalence in some populations, such as persons living with HIV and others immunoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 105 publications
(130 reference statements)
3
20
0
1
Order By: Relevance
“…The percentage of incidence of isolated HBc-Ab serologic profile pattern was detected as 22.58 % in such patients. These results agree with Moretto et al, (2020) who declared that the increased prevalence of isolated HBc-Ab is associated with HCV infection (Moretto et al, 2020). Also, these results are slightly agreed with Bhattacharya et al, (2016), who reported the percentage of incidence of isolated HBc-Ab serologic profile pattern as 31 % in HCV-patients coinfected with HIV, they concluded that the higher incidence of isolated HBc-Ab was associated with HCV rather than HIV infection.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The percentage of incidence of isolated HBc-Ab serologic profile pattern was detected as 22.58 % in such patients. These results agree with Moretto et al, (2020) who declared that the increased prevalence of isolated HBc-Ab is associated with HCV infection (Moretto et al, 2020). Also, these results are slightly agreed with Bhattacharya et al, (2016), who reported the percentage of incidence of isolated HBc-Ab serologic profile pattern as 31 % in HCV-patients coinfected with HIV, they concluded that the higher incidence of isolated HBc-Ab was associated with HCV rather than HIV infection.…”
Section: Discussionsupporting
confidence: 88%
“…Recent findings refer that the isolated anti-HBc pattern is a serologic profile, which mostly indicates past exposure regarding HBV with lacking the development of HBs-Ab immunity (Moretto et al, 2020). Some studies referred to the association of incidence of such serologic profile with those patients who were particularly exposed to HCV infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, those with serological evidence of resolved infection (anti-HBc-positive/anti-HBs-positive) should receive pre-emptive therapy. Advised NUCs are those at high genetic barrier of resistance (i.e., entecavir or tenofovir) due to the long duration of treatment or prophylaxis [25]; treatment of chronic HBV hepatitis with NUCs should continue until virological response (i.e., HBsAg loss with anti-HBs seroconversion), whereas anti-viral prophylaxis and pre-emptive therapy should continue for at least 12 months (18 months for rituximab) after discontinuation of immunosuppressive treatment [6,26]. The patients herein described have received antiviral therapy or periodical monitoring, based on the serological status and according to the 2012 EASL report [27], and cases of reactivation during immunosuppressive therapy have not yet been observed.…”
Section: Discussionmentioning
confidence: 99%